Identification and characterization of centromeric sequences in Xenopus laevis - Smith, Owen K.; Limouse, Charles; Fryer, Kelsey A.; Teran, Nicole A.; Sundararajan, Kousik; Heald, Rebecca; Straight, Aaron F.

(untitled) (Genome Research, 2021)
Centromeres play an essential function in cell division by specifying the site of kinetochore formation on each chromosome for mitotic spindle attachment. Centromeres are defined epigenetically by the histone H3 variant Centromere Protein A (Cenpa). Cenpa nucleosomes maintain the centromere by designating the site for new Cenpa assembly after dilution by replication. Vertebrate centromeres assemble on tandem arrays of repetitive sequences, but the function of repeat DNA in centromere formation has been challenging to dissect due to the difficulty in manipulating centromeres in cells. Xenopus laevis egg extracts assemble centromeres in vitro, providing a system for studying centromeric DNA functions. However, centromeric sequences in Xenopus laevis have not been extensively characterized. In this study, we combine Cenpa ChIP-seq with a k-mer based analysis approach to identify the Xenopus laevis centromere repeat sequences. By in situ hybridization, we show that Xenopus laevis centromeres contain diverse repeat sequences, and we map the centromere position on each Xenopus laevis chromosome using the distribution of centromere-enriched k-mers. Our identification of Xenopus laevis centromere sequences enables previously unapproachable centromere genomic studies. Our approach should be broadly applicable for the analysis of centromere and other repetitive sequences in any organism.